Clinical utility of decarboxylation prothrombin combined with α-fetoprotein for diagnosing primary hepatocellular carcinoma. Issue 5 (5th October 2018) - Fu, Jun; Li, Yanyan; Li, Zhanzhan; Li, Na
Abstract : We conducted a comprehensive analysis to evaluate clinical utility of decarboxylation prothrombin combined with α-fetoprotein (AFP) for diagnosing primary hepatocellular carcinoma (HCC). Systematical searches were performed in PubMed, Web of Science, China National Knowledge Internet, and Wangfang databases. The bivariate random-effect model was used to calculate the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood, diagnostic odds ratio (DOR), and summary area under the curve (AUC). Fourteen studies were included in the meta-analysis. For decarboxylation prothrombin, the overall pooled parameters are as follows: sensitivity: 79% (95% confidence interval (CI): 74–84%), specificity: 91% (95%CI: 87–93%), PLR: 8.42 (95%CI: 5.79–12.23), negative likelihood ratio (NLR): 0.23 (95%CI: 0.17–0.30), DOR: 37.09 (95%CI: 21.37–64.36), summary AUC: 0.92 (95%CI: 0.89–0.94); for combined diagnostic, the overall pooled parameters were as follows: sensitivity: 91% (95%CI: 85–95%), specificity: 83% (95%CI: 74–89%), PLR: 5.26 (95%CI: 3.53–7.83), NLR: 0.11 (95%CI: 0.07–0.18), DOR: 47.14 (95%CI: 30.09–73.85), summary AUC: 0.94 (95%CI: 0.91–0.95). The serum decarboxylation prothrombin showed a relatively higher diagnostic specificity for primary HCC and decarboxylation prothrombin combined with AFP exhibited can improve sensitivity for HCC than any of the biomarkers alone.